(untitled) (Bangladesh Pharmaceutical Journal, 2020)
Diabetes mellitus (DM), characterized by chronic hyperglycemia is one of the most common chronic diseases affecting millions of people worldwide. A significant component of the risk associated with DM is thought to be because of its abnormal lipid ‘triad’ profile. All the associated complications are mainly due to imbalance between generation of free radicals and the antioxidant systems like catalase (CAT) and super oxide dismutase (SOD) enzymes. Moreover, increased level of serum glutamate pyruvate transaminase (SGPT) and serum glutamate oxaloacetate transaminase (SGOT) are considered a consequence of hepatocyte damage. The current study was designed to investigate the antihyperglycemic and antidyslipidemic effects, oxidative stress and liver dysfunction indices of fixed dose combination therapy of sitagliptin [50 mg/70kg body weight (BW)] and β-carotene (5 mg/70kg BW) on streptozotocin (45 mg/kg BW) induced diabetic rats (SIDRs). The study showed that combination therapy induced a significant decrease in blood glucose level (BGL) from 19.09 ± 0.13 to 6.86 ± 0.11 mmol/l in comparison to the control group after daily treatment for three weeks. In case of dyslipidimic effect, combination therapy reduced total cholesterol (TC) (22.96%), triglycerides (TG) (17.54%) and low-density lipoprotein (LDL)-cholesterol (52.25%) levels significantly and increased high-density lipoprotein (HDL)-cholesterol level (55.98%) in comparison with respective diabetic control groups. We also observed that combination therapy lowered SGPT & SGOT level by 46.39% and 37.23%, respectively and increased SOD & CAT enzyme activity by 63.79% and 48.32%, respectively in comparison with diabetic control groups. These changes were significantly better than those of sitagliptin and β-carotene monotherapy. The suggestions of our findings of this research are that combination therapy is more potent than their individual monotherapy and may be beneficial for the treatment of diabetic patients with associated complications. Bangladesh Pharmaceutical Journal 23(2): 87-95, 2020